Les paysages de Kronsberg à Hanovre : approches sonore et multisensorielle - Élise Geisler; Théa Manola (Projets de Paysage)
Actually, in the plentiful scientific production on the landscape question, but also in the speeches of the landscape architects, the multisensoriality of the landscape is considered as acquired. However, almost no specific check was made by research works, in spite of the invitations in the fields of the research and the founding works on the mono-sensory landscapes concerning the other senses that the sight. This article presents the first results of a crossed analysis, in terms of methodological contributions, of three research works : a research led within the framework of the Pirve financed by the Puca and CNRS, and phd researches of E. Geisler and of T. Manola. These three researches adopt a sensitive approach of the landscape with similar methods (interviews, commented courses, sound journal/multisensory bag). For the precise case of the sustainable neighborhood of Kronsberg in Hanover, we are going to try to present the state of progress of our works concerning the methodological part and to determine the contributions and the complementarities of the various methods, as well as the difficulties met for each of them. We shall also compare both, almost identical protocols (applied on one hand to the sound and on the other hand to the multisensory) and shall try to see the advantages of the one and the other one.